Танки - Бакурский Виктор Александрович (Детская энциклопедия РОСМЭН, 2021)
Экземпляры: ф.5 (2021) / Инвентарный номер: 57453 / Цена: / Сис.шифр: 68.513я2 / Авт.знак: Б 19 / ГРНТИ: 78.25 / ББК: 68.513 я2